REDISEÑO DE LA DISTRIBUCIÓN DE PLANTA EN EL TALLER INDUSTRIAL EL ENGRANAJE, PARA OPTIMIZAR LA PRESTACIÓN DE SERVICIOS METAL MECÁNICOS EN EL CANTÓN QUEVEDO - Bravo Arzube, Carlos Andres (2023)
In the company El Engranaje, an investigation was carried out to improve production through redistribution in the plant. Objectives were established to redistribute the areas in line with the company's production and a flow and route diagram was prepared to identify the equipment, machines, operators and materials involved in the manufacture of doors, gates and pulleys.